Shared decision-making (SHARE-D) for healthy behaviour change: a feasibility study in general practice - Margaret E Cupples; Judith A Cole; Nigel D Hart; Neil Heron; Michelle C McKinley; Mark A Tully (BJGP Open, 2018)
Background: Effective interventions are needed to support health behaviour change for cardiovascular disease (CVD) prevention. Decision tools encourage behaviour change but their effectiveness when used in shared decision-making with health professionals (HPs) is unknown. Aim: To test the feasibility of using a novel, paper-based tool for shared decision-making in initiating behaviour change. Design & setting: A feasibility study in five general practices in Northern Ireland. Method: Adults with, or at high risk of, CVD were invited to discuss their diet and physical activity (PA) with an HP. Using a paper-based decision aid in shared decision-making about behaviour change, their capabilities, opportunities, and motivation were considered. Diet and PA were assessed at baseline, 1, and 3 months using the Dietary Instrument for Nutritional Education (DINE) and the Recent Physical Activity Questionnaire (RPAQ); accelerometers measured PA at baseline and 3 months. Semi-structured interviews, analysed thematically, explored participants’ and HPs’ views of the process.Results: The positive response rate to study invitation was 28% (45/162); 23 were recruited (aged 43–74 years; 50% male; <40% met diet or PA recommendations); and 87% (20/23) completed the study. All interviewees valued the tool’s structure, succinct content, and facilitation of discussion. HPs’ sharing of relevant personal experience encouraged behaviour change; social responsibilities, health conditions, and beliefs restricted change. HPs’ workloads prohibited the tool’s routine use. Conclusion: Recruitment and completion rates suggest that using a novel, paper-based tool in shared decision-making for behaviour change is feasible. HPs’ workloads constrain its use in practice, but qualitative findings indicate its potential value. Cross-sector collaborative exploration of sustainable models to promote behaviour change is needed.